PENGARUH LITERASI KEUANGAN DAN PREFERENSI RISIKO TERHADAP NIAT INVESTASI DENGAN APLIKASI INVESTASI DIGITAL: THE IMPACT OF FINANCIAL LITERACY AND RISK PREFERANCE ON INVESTMENT IN DIGITAL INVESTMENT APPLICATION - Dewi Kusuma Wardani; Gading Putri Eka Wati (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
Invesment can be defined as investment activity. Investment in human civilization is not new because people have been investing since ancient times. This study was conducted to identify the correlation between financial and risk preferences on student intention to invest on the digital investment application. Data in this research was obtained from 151 respondent student in Yogyakarta with quantitive description method and primary data in the forms questions. Sample in this study was obtained by using convienence sampling technique. The result of this study demonstrate that financial literacy and risk prefereance have a positive effect on investment intentions in digital investment application. For this reason bursa efek can work with universities to provide insight into the use of online stock trading